Evaluation of Road Preservation Priorities Based on Road Condition and Traffic Load on the Jambi Province Border-Maur Project Corridor - Pratiwi, Kimgrace Martha Putri; Handayani, Dewi; Hartono, Widi (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2026)
This study aims to evaluate road preservation priorities based on road surface condition and traffic load along the Jambi Province Border–Maur project corridor. The dataset comprises maintenance cost data for ten road sections. The analysis was conducted by calculating the maintenance cost per kilometer, applying min–max normalization to the International Roughness Index (IRI) and Average Daily Traffic (ADT), and developing a Service Pressure Index (SPI). The results indicate that the Betung–Bts. Kota Palembang section has the highest preservation priority, with an SPI value of 0.953, followed by the Bts. Prov. Jambi–Peninggalan section with an SPI value of 0.623 and the Sei Lilin–Betung section with an SPI value of 0.431. These findings suggest that the SPI can serve as an initial decision-support tool for establishing road preservation priorities in a more proportional manner by considering both infrastructure condition and service pressure.